Advances in the understanding of ocular blood flow in glaucoma. (April 2010) - Shoshani, Yochai Z; Harris, Alon; Siesky, Brent A
Although intraocular pressure remains the only current treatable risk factor in open-angle glaucoma, several other risk factors have been reported, including insufficient ocular blood flow and low perfusion pressure. Over the past several decades, significant progress has been made in the methodologies utilized to assess ocular blood flow as well as consensus in interpreting their results. Utilizing these devices, dozens of prospective investigations have revealed altered ocular blood flow, ocular perfusion pressure and faulty vascular regulation in patients with open-angle glaucoma. Pilot research studies have found reductions in ocular circulation to be associated with various markers of structural and functional glaucoma progression. However, these pilot studies have been limited in size, scope and execution, and only larger, multicentered prospective controlled studies are capable of providing definitive proof of the vascular role in glaucoma progression.